Economic populism under pressure: NGOs and the new capitalist ethos in Indonesia - Chalmers, Ian (Australian National University, 1996)
A common theme within Indonesian studies in recent years has been the gradual dimunition of state control in various aspects of social life. Political economists have given particular attention to the erosion of state domination of the economy, and noted a corresponding increase in the political influence of the business sector (Robison 1986, Soesastro 1989, MacIntyre 1992). This development is significant, because for historical reasons the Indonesian political culture has fostered widespread suspicion of capitalism and a general faith in the capacity of the state to advance the common good. During the emergence of Indonesian nationalism in the early decades of this century capitalism came to associated with colonialism and imperialism. In the two decades following the declaration of independence in 1945 various social movements further encouraged this antipathy towards economic individualism, and a number of measures were taken to bring the economy under popular control. Today, senior public figures still frequently express their opposition to 'free-fight liberalism' and the depredations that would occur if the market was allowed to operate unhindered. In this light, the recent retreat of the state from the economy has important ideological implications, and it is the purpose of this paper to explore the impact of economic deregulation and liberalisation on economic thinking.